1999
DOI: 10.1136/thx.54.7.597
|View full text |Cite
|
Sign up to set email alerts
|

Association of air pollution with daily GP consultations for asthma and other lower respiratory conditions in London

Abstract: Background-Very few published studies have looked at the eVects of air pollution on health in the primary care setting. As part of a large study to examine the association between air pollution and a number of health outcomes, the relationship between daily GP consultations for asthma and other lower respiratory diseases (LRD) and air pollution in London was investigated. Methods-Time-series analysis of daily numbers of GP consultations controlling for time trends, seasonal factors, day of week cycles, influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
80
1
5

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(97 citation statements)
references
References 12 publications
11
80
1
5
Order By: Relevance
“…A significant correlation was noted between air pollution in the province and the number of asthma cases [40]. In an analysis conducted on adults and children in London, it was shown that PM10 and SO 2 had strong effects on asthma and other lower respiratory tract diseases [41]. In our study, the findings revealed an increasing linear relationship between the levels of PM10 and SO 2 and the number of patient admissions for COPD.…”
Section: Discussionsupporting
confidence: 61%
“…A significant correlation was noted between air pollution in the province and the number of asthma cases [40]. In an analysis conducted on adults and children in London, it was shown that PM10 and SO 2 had strong effects on asthma and other lower respiratory tract diseases [41]. In our study, the findings revealed an increasing linear relationship between the levels of PM10 and SO 2 and the number of patient admissions for COPD.…”
Section: Discussionsupporting
confidence: 61%
“…For example, it is likely that persons with private health insurance are also affected by air pollution, but can afford to visit a private physician before the effects become more severe to necessitate a hospital admission. Indeed, recent papers have reported air pollution associations with doctors' visits among the general population (24,25). Unfortunately, private doctor visits counts are not publicly available for New York City, so we could not test for wider, less severe, effects in this population as part of this work.…”
Section: Discussionmentioning
confidence: 99%
“…Another study revealed increased effects of NO2 when other pollutants were included in the models (Sunyer et al (1997)). The debate continues, although recent studies have again found effects of NO2 , Hajat et al (1999), Garcia et al (2000)). …”
Section: Urban Air Quality Revisitedmentioning
confidence: 99%